CHRONIC INTERACTION BETWEEN METFORMIN AND MELOXICAM IN MICE - AL-REKABI, FALAH MUOSA KADHIM (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: This study is performed for investigation the chronic interaction between metformin and meloxicam from toxicological view. Methods: Lethal dose 50 after chronic exposure assessed in mice by up and down method. Their interaction analyzed by isobolographic analysis indicated that both medicines exhibited synergism. Assessment of the effects of repeated chronic dosing for 3 months of both medicines also performed on mice. Medicines in question administered orally as therapeutic doses of metformin 14 mg/kg. Body weight (BW) (G1), meloxicam 0.2 mg/kg.BW (G2), and combination of both medicines (G3) while G4 assigned control and dosed DW. Results: Both G1 and G3 showed significant p˂0.05 decrease in blood glucose and serum cholesterol levels. Meloxicam group (G3) showed statistically significant p˂0.05 increase in triglycerides and alanine aminotransferase (ALT), and aspartate aminotransferase (AST), while group of combination showed statistically significant p≤0.05 decrease in both ALT and AST. Blood urea nitrogen, uric acid, and serum creatinine showed statistically significant p˂0.05 increase in group of meloxicam but decrease in G3 and no changes in G1. Histopathological changes included variable lesions in kidney such as swelling and necrosis in renal tubules of metformin group, cortical vacuolar degeneration in renal tubules, and deterioration of most glomeruli in G2, while G3 showed generalized cortical necrosis of renal tubules and interstitial nephritis. Liver lesions included central venous congestion (VC) and perivascular lymphocytic infiltration and marked necrosis in both groups of metformin and meloxicam, while there were severe VC and necrosis of hepatocytes in group of combination. Conclusion: Metformin administration with meloxicam may have beneficial important through preventing many deleterious effects of meloxicam after long-standing administration, but adjusting dosing regimen study might be recommended.